The economic impact of clinically significant tricuspid regurgitation in a large, administrative claims database. (3rd May 2020) - Cork, David P.; McCullough, Peter A.; Mehta, Hirsch S.; Barker, Colin M.; Van Houten, Joanna; Gunnarsson, Candace; Ryan, Michael P.; Baker, Erin R.; Mollenkopf, Sarah; Verta, Patrick
Abstract: Aim: This study aimed to quantify the healthcare burden of clinically significant tricuspid regurgitation (TR) in patients with and without heart failure (HF). Materials and Methods: Data were from the IBM MarketScan Research Databases from October 2011 to September 2016. Eligible patients met the following inclusion criteria: age ≥18 with a TR diagnosis, 12 months pre (baseline), and 6 months post (landmark) medical enrollment. The landmark period was used to categorize TR severity, defined as a record of pulmonary hypertension with ascites, lower extremity edema or hepatic insufficiency, or tricuspid valve surgery. Cohorts were defined based on TR etiology and severity: (1) no HF and no clinically significant TR; (2) HF with no clinically significant TR; (3) no HF with clinically significant TR; and (4) HF with clinically significant TR. Outcomes of interest were all-cause hospitalizations, hospital days, and expenditures. Multivariable models were fit for each of the annualized outcomes and adjusted for patient demographics, comorbidities, and other concomitant valve diseases. Results: There were 92, 994 patients eligible for analysis. Patients with no HF and no clinically significant TR had the annualized healthcare burden of 0.20 all-cause hospitalizations (approximately one inpatient hospitalization every 5 years), 1.07 hospital days, and $17, 478 in expenditures. The presence of clinically significant TR, alone or with HF, significantly increased healthcare utilization and expenditures. For patients with no HF with clinically significant TR, the annualized economic burden increased to 0.41 all-cause hospitalizations, 3.13 hospital days, and $29, 985 in expenditures. For patients with HF and clinically significant TR, the annualized economic burden was even greater with 0.59 all-cause hospitalizations, 4.31 hospital days, and $42, 255 in expenditures. Conclusion: The presence of clinically significant TR is associated with an increase in healthcare utilization and expenditures, irrespective of the presence of HF.